Modern trends in organizational management for achieving sustainable development: green course and innovations (Economics and region, 2025)
The article considers the issue of managing organizations in the context of transition to sustainable development and implementation of the principles of the green course. The relevance of this topic, due to global environmental challenges, is substantiated. The need to introduce innovations to increase the efficiency of resource use is proven. The main challenges are considered: air pollution, water resources, biodiversity loss, waste accumulation and climate change. It is emphasized that these problems affect all sectors of the economy, in particular agriculture, logistics, manufacturing and financial markets, which necessitates their consideration during strategic planning. Special attention is paid to the European Green Deal as a comprehensive strategy for sustainable development, which provides for decarbonization, resource efficiency and social inclusion. The role of innovations, in particular alternative energy, in achieving environmental goals is revealed, using the example of the Botievka WPP and the Tyligul WPP, as well as the use of artificial intelligence by the Kernel company to optimize agricultural production. It is emphasized that the combination of environmental responsibility and an innovative approach ensures competitiveness, long-term sustainability and the ability of companies to function effectively even in crisis conditions. Practical examples of the implementation of environmental and innovation strategies are analyzed using examples of domestic and international companies that demonstrate effective integration of the principles of sustainable development into the corporate governance system. The role of the experience of the European Union is determined, in particular within the framework of the European Green Deal initiative. The formation of a new managerial mindset focused on the balance between economic efficiency, innovation and environmental sustainability, the possibility of combining business goals with responsibility to society and the environment is considered.
Keywords: organizational management; implementation of innovations; green course; sustainable development of organizations; efficiency improvement; environmental initiatives